Polyacrylonitrile‑b‑poly(butyl acrylate) Block Copolymers as Precursors to Mesoporous Nitrogen-Doped Carbons: Synthesis and Nanostructure - Kopeć, Maciej; Yuan, Rui; Gottlieb, Eric; Abreu, Carlos M. R; Song, Yang; Wang, Zongyu; Coelho, Jorge F. J; Matyjaszewski, Krzysztof; Kowalewski, Tomasz (Macromolecules, 2017)
A series of polyacrylonitrile-block-poly(butyl acrylate) (PAN-b-PBA) copolymers were prepared by supplemental activator reducing agent atom transfer radical polymerization (SARA ATRP). These copolymers were then used as precursors to pyrolytic nanostructured carbons with the PAN block serving as a nitrogen-rich carbon precursors and the PBA block acting as a sacrificial porogen. The study revealed that while the size of mesopores can be controlled by the size of the porogenic block, the connectivity of pores diminishes with the decrease of the overall molecular weight of the precursor. This partial loss of mesopore connectivity was attributed to the weaker phase segregation between the blocks of shorter lengths inferred from the shape of small-angle X-ray scattering profiles and from the crystallinity of polyacrylonitrile phase.